Pola Fungsi Kalimat pada Novel “Pulang” Karya Tere Liye dan Kelayakannya sebagai Materi Pengayaan Siswa Kelas Xll SMA - Muchammad Akbar Ibrani; Angelica Hexa Trinita Pandiangan; Titis Abhirama Reswara; Moch. Yusuf Ilham Noer; Haula Inayatul Ilahiyah; Asep Purwo Yudi Utomo; Qurrota Ayu Neina (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Understanding sentence function patterns plays a major role in reading a novel, especially in class XII. By studying the understanding of sentence function patterns, class XII students can understand the important role of sentence function patterns in a novel. This research aims to be an informative and interesting learning resource for class XII students to use novels as enrichment material and improve their language skills. This research considers the function patterns of sentences in the novel